Influence of Eu-substitution on luminescent CH3NH3PbBr3 quantum dots. Issue 24 (11th June 2018) - Liu, Lijia; Li, Jitao; McLeod, John A.
Abstract : Eu-Substitution in MAPbBr3 reduces toxicity, increases crystallinity, and provides blue photoluminescence. Abstract : We report a series of Eu-substituted methylammonium lead tribromide quantum dots (MAPb1− x Eu x Br3 QDs). The crystallinity of these QDs increases with increasing Eu content, while there is only a small change in the lattice constant, and the morphology of the MAPb1− x Eu x Br3 QDs is unaffected by the Eu content. This demonstrates that Eu is a suitable element for substituting Pb while retaining the original crystal structure. We observe blue photoluminescence (PL) consistent with Eu 2+, which, at high Eu content ( x = 0.3), contributes luminescence intensity equal to the green PL of unsubstituted MAPbBr3 QDs. As Eu is a less toxic substitute for Pb, that also provides blue luminescence, MAPb1− x Eu x Br3 QDs may prove to be a valuable optoelectronic material.